THE EFFECTIVENESS OF SCIENCE LITERACY CULTURE THROUGH ENCYCLOPEDIC TEACHING MATERIALS IN SCIENCE LEARNING AT ELEMENTARY SCHOOLS IN WEST JAKARTA - Erdhita Oktrifianty; Rizki Zuliani; Een Unaenah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study emphasized the importance of teaching materials to improve the culture of scientific literacy in science learning through encyclopedic books. Thus, scientific literacy was fostered among students as well as between teachers and students through the use of teaching materials. The encyclopedic teaching materials were tailored to students’ interests with the aim of creating a culture of scientific literacy. The purpose of this study was to determine the learning outcomes and scientific literacy abilities of fifth-grade students after using encyclopedic teaching materials. The research method used in this study was action research, in which the researchers acted as collaborators while teachers served as implementers of the action. This study was conducted at three elementary schools in West Jakarta. The object of the study was the science subject at grade V of elementary school, which was developed in the form of encyclopedic teaching materials. The results of this study showed an improvement in science learning, particularly on the topics of the human movement system, human respiratory system, and human circulatory system, through the use of encyclopedic teaching materials. It was recommended that teachers cultivate students’ literacy through encyclopedic teaching materials in other subjects in order to facilitate students in the learning process.